ROAD ACCIDENT FUND STEPS INTO THE SHOES OF THE INSURED OWNER: Road Accident Fund v Abrahams (276/2017) [2018] ZASCA 49 (29 March 2018) - Darren Subramanien; Tamera Govender (Obiter, 2019)
The Supreme Court of Appeal (SCA) in Road Accident Fund v Abrahams (276/2017) [2018] ZASCA 49 (29 March 2018) had to decide whether a driver involved in a single motor vehicle accident and who was not an employee of the owner of the insured vehicle was entitled to claim compensation from the Road Accident Fund (the Fund). The facts in the case differed from the usual scenario where two vehicles collide. In the present case, it was the negligent or wrongful conduct of the owner of the vehicle that the party relied upon to sue the Fund. As such, in this case, the focus of liability was not on the driver‚ but on the insured owner.